PUSAT SENI PERTUNJUKAN DENGAN PENDEKATAN EKO KULTURAL DI SURAKARTA - Muhammad Faruq Rizky Ardianto; Hardiyati Hardiyati; Agus Heru Purnomo (Universitas Sebelas Maret Surakarta, 2015)
Along the time, the performing art is not just a mere entertainment but also as a necessity for the modern man. Surakarta is the city with the development of the cultural and artistic performance's development,starting from kethoprak, wayang and keroncong that develops and be born in this city. the problem of the design is to create a character from Eco-Cultural element of Javanese culture and environment friendly, to the performing arts building. The problem of the design is how to achieve a performance art in accordance with the changing times which does not leave the local cultural elements. the design method used is the method of approach in order to create a container Eco Cultural arts activities that are capable of adapting to the changing times but still consider the local culture and environment friendly. Result obtained in the form of design cultured Center for the Performing Arts and as an application of enviromentally friendly Eco Cultural character. Building Performing Arts Center is expected as container performing arts activities in Surakarta.Keyword : Eco Cultural, Perfomance Art